Policy Model Reconstruction of Social Forestry - Wartiningsih Wartiningsih; Nunuk Nuswardani (Sriwijaya Law Review, 2021)
Internationally, there has been a paradigm shift in forest resource management from state-based forest management to community-based forest management. This change has also occurred in Indonesia, namely through the social forestry program as outlined in the the Minister Regulation on Social Forestry and the Minister Regulation on Social Forestry in Perhutani Area. Indeed, these Ministerial Regulations already contain the principles of community-based forest management. However, the implementation still leaves problems. This paper will analyze the procedural weaknesses and inaccuracies in the designation of these Ministerial Regulations. The approach used is the statutory approach and comparison with qualitative analysis. The result shows that it is necessary to change the policy model by changing procedures by re-functioning the role of Forest Management Units as an institution that has the authority to manage forest resources in its area. Besides, the Social Forestry program should only be intended for forest communities who have pioneered forest resource management, whether they have joined the Community Joint Forest Management program or not. However, they must reside around forests managed by Perum Perhutani.